Effectiveness of Local Music Learning Using Audio Visual Media - Madoni, Ricko Anggara; Marzam (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to determine and describe the students' ability to learn local music by using audio-visual media. The type of research is qualitative with a descriptive approach. The instrument of this research is the researcher himself by using tools such as stationery and cameras. Data were collected through observation and interviews. The stages of data analysis are data collection, data reduction, and data inference. The results prove that students more easily understand/master the practice of playing local traditional musical instruments (talempong pacik) in learning when the teacher not only lectures, but also uses audio-visual media. In addition, by dividing student groups, the implementation of learning also becomes more effective.